Pengaruh Lingkungan Belajar dan Motivasi Belajar Terhadap Keaktifan Belajar Siswa Sekolah Dasar - Nuha, Faliq Dziy; Anggriana, Tyas Martika; Cristiana, Ratih (Tarqiyatuna: Jurnal Pendidikan Agama Islam dan Madrasah Ibtidaiyah, 2022)
In learning activities, the involvement of students is very important in order to explore their potential. There are many factors that influence the activeness of students, one of which is learning motivation and learning environment. The objectives of this research are 1) to determine the effect of the learning environment on learning activities in fifth grade students at SDN Bangunsari 02. 2) to determine the effect of learning motivation on learning activities in fifth grade students at SDN Bangunsari 02. 3.) To determine the effect of learning environment and learning motivation simultaneously affect the learning activity of the fifth grade students of SDN Bangunsari 02. In this research using quantitative research methods, the sample of this study amounted to 88 students. The results of this study are a) The learning environment has a positive and significant effect on student learning activities at SDN Bangunsari 02 academic year 2022/2023 simultaneously by 0.56%. b) Learning motivation has a positive and significant effect on student learning activities at SDN Bangunsari 02 for the academic year 2022/2023 simultaneously by 11.1%. c) The learning environment and learning motivation together have a positive and significant effect on student learning activities at SDN Bangunsari 02 for the academic year 2022/2023. 11.1% While the remaining (100% - 11.1%) = 88.9% is explained by other factors outside the model studied.